Is competitive body-building pathological? Survey of 984 male strength trainers - Ian Steele; Harrison Pope; Eric J Ip; Mitchell J Barnett; Gen Kanayama (BMJ Open Sport & Exercise Medicine)
Objectives Hundreds of thousands, if not millions, of individuals worldwide engage in competitive body-building. Body-building often attracts derogatory characterisations such as as ‘bizarre’ or ‘narcissistic,’ or a ‘freak show’, seemingly implying that it is associated with pathology. Few studies have compared psychological features in competitive bodybuilders versus recreational strength trainers.Methods Using logistic regression with adjustment for age and race, we compared 96 competitive bodybuilders (‘competitors’) with 888 recreational strength trainers (‘recreationals’), assessed in a prior internet survey, regarding demographics; body image; use of anabolic–androgenic steroids (AAS), other appearance-enhancing and performance-enhancing drugs (APEDs), and classical drugs of abuse; history of psychiatric diagnoses; and history of childhood physical/sexual abuse.Results Competitors reported a higher lifetime prevalence of AAS (61 (63.5%) vs 356 (10.1%), p<0.001) and other APED use than recreationals but showed very few significant differences on other survey measures. AAS-using competitors were more likely than AAS-using recreationals to have disclosed their AAS use to a physician (31 (50.8%) vs 107 (30.0%), p=0.003). Both groups reported high levels of body image concerns but did not differ from one another (eg, ‘preoccupation with appearance’ caused significant reported distress or impairment in important areas of functioning for 18 (18.8%) competitors vs 132 (15.4%) recreationals, p=0.78). No significant differences were found on the prevalence of reported childhood physical abuse (9 (9.4%) vs 77 (8.8%), p=0.80) or sexual abuse (4 (4.2%) vs 39 (4.5%), p=0.83). Competitors reported a lower lifetime prevalence of marijuana use than recreationals (38 (39.6%) vs 514 (57.9%), p=0.001).Conclusion Aside from their APED use, competitive bodybuilders show few psychological differences from recreational strength trainers.